Предмет: Математика,
автор: Lukashevich333
Решите пожалуйста !!!
Приложения:
Ответы
Автор ответа:
0
1) (х-3)/2=(1-4х)/3
(3х-9)/6=(2-8х)/6
3х-9=2-8х
3х+8х=2+9
11х=11
х=11:11
х=1
(3х-9)/6=(2-8х)/6
3х-9=2-8х
3х+8х=2+9
11х=11
х=11:11
х=1
Автор ответа:
0
(x-3)*3=2*(1-4x)
3x-9=2-8x
3x+8x=2+9
11x=11
x=1
3x-9=2-8x
3x+8x=2+9
11x=11
x=1
Похожие вопросы
Предмет: Другие предметы,
автор: asylaikenzhebai
Предмет: Литература,
автор: Аноним
Предмет: Английский язык,
автор: yashenkolrina2000
Предмет: Геометрия,
автор: OctoberDay